2016
DOI: 10.12974/2309-6128.2016.04.1
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Nitric Oxide as A Signaling Molecule In Regulation of Subclinical Inflammation and Apoptosis in Hypertensive Elderly Patients

Abstract: Nitric oxide (NO) is a universal regulator of different processes, including vascular tone, hemostasis ?nd apoptosis. One of the important functions of NO as a signaling molecule is determined by a high capacity for diffusion through the cell membrane to synthesize it and penetrate into target cells by controlling their metabolism ?nd realizing intercellular interactions. For the purpose of estimation in elderly persons due to for determine the effect of nitric oxide and its products on the process of subclini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Insulin resistance is another cause of concern. Gorshunova et al observed increased insulin resistance indices in hypertensive patients with low muscle mass and strength, accompanied by signs of left ventricular myocardial dysfunction and HF, possibly due to glucose entering the heart and skeletal muscle cells [ 33 ]. Malnutrition is another contributing factor.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance is another cause of concern. Gorshunova et al observed increased insulin resistance indices in hypertensive patients with low muscle mass and strength, accompanied by signs of left ventricular myocardial dysfunction and HF, possibly due to glucose entering the heart and skeletal muscle cells [ 33 ]. Malnutrition is another contributing factor.…”
Section: Discussionmentioning
confidence: 99%